Outcomes and patterns of failure of sarcomatoid carcinoma of the larynx: The Mayo Clinic experience. (6th July 2017) - Gamez, Mauricio E.; Jeans, Elizabeth; Hinni, Michael L.; Moore, Eric; Young, Geoffrey; Ma, Daniel; McGee, Lisa; Buras, Matthew R.; Patel, Samir H.
Abstract : Objectives/Hypothesis: Sarcomatoid carcinoma is a rare variant of squamous cell carcinoma of the head and neck. No consensus exists on its management. Our aim was to present our outcomes. Study Design: Retrospective study. Median follow‐up 45 months. Methods: There were 38 patients with pathologically confirmed sarcomatoid carcinoma of the larynx treated at the Mayo Clinic from 1990 to 2014. Statistical analysis of overall survival (OS), progression‐free survival (PFS), and local control (LC) were conducted using the Kaplan‐Meier method. Results: The majority of patients were elderly males (92%) with a smoking history (74%) presenting with early‐stage disease (71%). Surgery alone was the primary treatment in 27 patients (71%). Nine patients (25%) were treated with adjuvant radiation due to initial stage or high‐risk pathologic features. Median radiation dose to the primary/surgical bed was 65 Gy (range, 60.3–75.0 Gy). A total of 15 patients (39%) had tumor recurrence, majority being local (n = 12). Sixty percent (n = 9) had multiple local recurrences. Five‐year OS, PFS, and LC were 63%, 46%, and 72%, respectively. Subgroup analysis by stage I versus higher stages (II–IV) showed an OS of 80% versus 43% ( P = .030), PFS of 65% versus 18% ( P = .003), and LC of 84% versus 57% ( P = .039). Conclusions: Sarcomatoid carcinoma of the larynx is rare, and frequently presents at an early stage in older men with history of smoking. Based on our outcomes and patterns of failure, it appears early‐stage tumors are treated appropriately with single‐modality therapy, whereas more advanced tumors require multimodality therapy. Validation in a larger cohort is warranted. Level of Evidence: 4. Laryngoscope, 128:373–377, 2018